Indoleamine 2,3-dioxygenase–expressing dendritic cells form suppurative granulomas following Listeria monocytogenes infection - Alexey Popov; Zeinab Abdullah; Claudia Wickenhauser; Tomo Saric; Julia Driesen; Franz-Georg Hanisch; Eugen Domann; Emma Lloyd Raven; Oliver Dehus; Corinna Hermann; Daniela Eggle; Svenja Debey; et al. (The Journal of Clinical Investigation, 2006)
Control of pathogens by formation of abscesses and granulomas is a major strategy of the innate immune system, especially when effector mechanisms of adaptive immunity are insufficient. We show in human listeriosis that DCs expressing indoleamine 2,3-dioxygenase (IDO), together with macrophages, are major cellular components of suppurative granulomas in vivo. Induction of IDO by DCs is a cell-autonomous response to Listeria monocytogenes infection and was also observed in other granulomatous infections with intracellular bacteria, such as Bartonella henselae. Reporting on our use of the clinically applied anti–TNF-α antibody infliximab, we further demonstrate in vitro that IDO induction is TNF-α dependent. Repression of IDO therefore might result in exacerbation of granulomatous diseases observed during anti–TNF-α therapy. These findings place IDO+ DCs not only at the intersection of innate and adaptive immunity but also at the forefront of bacterial containment in granulomatous infections.